The first geochemical data on pre-New-Euxinian deep sea deposits of the Black Sea. - Pilipchuk, Mikhail F; Sokolova, Ekaterina G; Golovina, M S (PANGAEA, 1980)
Geochemical data on New-Euxinian sediments and the first data on pre-New-Euxinian sediments of the Black Sea are reported in the paper. 4 meter long sediment core was collected in August 1977 during Cruise 61 of R/V Vityaz.
Chemical composition New-Euxinian and pre-New-Euxinian sediments from Core $, Black Sea
Keywords: Archive of Ocean Data; ARCOD; Black Sea; Calcium carbonate; Carbon, organic, total; DEPTH, sediment/rock; Epoch; GC; Gravity corer; Iron; Iron, reactive; Manganese; Molybdenum; Oxidation reduction (RedOx) potential; Sediment type; Selenium; Sulfur bound in sulfide; Titanium; Tungsten; VITYAZ; Vityaz (ex-Mars); VITYAZ7663; Water content, wet mass; Wet chemistry